At your service: supportiveness of servant leadership, communication frequency and communication channel fostering job satisfaction across generations - Coun, Martine J. H.; De Ruiter, Melanie; Peters, Pascale (Frontiers in Psychology, 2023)
The present study contributes to the conversations on the role of 'autonomy supportive' factors in employee wellbeing in remote work contexts by examining the relationships between servant leadership, communication frequency -overall and via synchronous (i.e., individual videocalls, individual telephone calls) and asynchronous communication channels (i.e., e-mail messages, and WhatsApp) -on the one hand, and job satisfaction, on the other, and the moderating role of generation (Baby Boomers and Gen X versus Gen Y) in these relationships.Building on self-determination theory, incorporating insights from servant leadership, telework, and media richness and synchronicity literatures, we developed hypotheses that were tested via multilevel analysis (273 employees nested in 89 managers). In line with expectations, servant leadership had a positive relationship with job satisfaction. Total communication frequency, however, was not related to job satisfaction. Further analyses per communication channel showed that only level 2 e-mail communication frequency was positively related to job satisfaction. In contrast to expectations, the relationships studied were not moderated by generation. We concluded that, for all generations, both servant leadership and frequent (email) communication can be regarded 'autonomy supportive' factors in employee wellbeing.Paradoxically, whereas servant leadership, considered as a human-centric leadership style, suggests close trust-based employment relationships, employees valued frequent asynchronous communication (via e-mail). Having access to information and knowledge when needed may satisfy employees' need for autonomy (and perhaps for flexibility to engage in work and nonwork activities). The insights gained in our study can inform organizations, managers, and employees, particularly in future remote work contexts.